Answer:
<u>The solution of this system of equation is ( 3, - 8)</u>
Step-by-step explanation:
1. Let's solve the system of equations:
First equation:
x + 2y = - 13
x = - 13 - 2y
Second equation:
12x + 5y = -4
12 * (- 13 - 2y) + 5y = - 4 (Replacing x with - 13 - 2y)
-156 -24y + 5y = - 4
-24y + 5y = - 4 + 156 (Like terms)
-19y = 152
y = - 152/19
<u>y = -8</u> (Dividing by 19)
Solving x
x + 2y = -13
x + 2 (- 8 ) = - 13
x - 16 = - 13
x = - 13 + 16
<u>x = 3</u>
2. Proving that x = 3 and y = - 8 are correct:
12x + 5y = -4
12 * 3 + 5 * -8 = -4
36 - 40 = - 4
- 4 = - 4
<u>We proved that x = 3 and y = - 8 are correct</u>
Answer:
4
Step-by-step explanation:
The mean of a set of data: <em>(n₁ + n₂ + n₃...)/n</em>, where n₁,₂,₃... are numbers in the set, and n is the number of numbers.
Plug in: (1 + 5 + 5 + 7 + 3 + 3 + 4)/7
Add: 28/7
Divide: 4
anna plis jangan tanya saya 1×7=7
5-2x=7-5x
-2x+5x=7-5
3x=2
X=2/3
Here is your answer and an explanation
Answer: y = -2/3x
Explanation:
This can be determined by calculating the gradient of the straight line, using:
m=ΔyΔx
=−6−34−(−2)
=−96
=−32
Then we use the slope-point form of the straight line:
y−y1=m(x−x1)
to give:
y−3=−32(x−(−2))
∴y−3=−32(x+2)
∴y−3=−32x−3
∴y=−32x